2019
DOI: 10.3390/ijerph16030472
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Home/Commercial Washing Strategies for Ten Typical Pesticide Residue Removal Effects in Kumquat, Spinach and Cucumber

Abstract: Home processing can reduce pesticide residues in agricultural products, and the common forms of treatment include washing, peeling, blanching, and cooking. In this study, the removal effects of tap water, micron calcium solution, alkaline electrolyzed water (AlEW), ozone water, active oxygen, and sodium bicarbonate on 10 typical pesticide residues in kumquat, cucumber, and spinach were investigated. The residue magnitudes were determined by chromatography–tandem mass spectrometry (GC-MS/MS, LC-MS/MS), combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 23 publications
2
37
0
Order By: Relevance
“…Reduced urinary levels of PYR metabolites were associated with washing fruits and vegetables with soda or hot water, but not when washed with saltwater or water (data not shown). In accordance with previous reports, washing fruits or vegetables with an alkaline solutions can effectively reduce pesticides on the surface [26,27]. PYRs are hydrophobic organic compounds (with high log P values) [28] and difficult to be washed-off with salt water or water.…”
Section: Aaem Annals Of Agricultural and Environmental Medicinesupporting
confidence: 89%
“…Reduced urinary levels of PYR metabolites were associated with washing fruits and vegetables with soda or hot water, but not when washed with saltwater or water (data not shown). In accordance with previous reports, washing fruits or vegetables with an alkaline solutions can effectively reduce pesticides on the surface [26,27]. PYRs are hydrophobic organic compounds (with high log P values) [28] and difficult to be washed-off with salt water or water.…”
Section: Aaem Annals Of Agricultural and Environmental Medicinesupporting
confidence: 89%
“…Consumers often use tap water or, worse, household chemicals designed and dedicated for other purposes. The result may be a very low efficiency of such a washing process 19 and likely the introduction of additional undesirable substances on the fruits’ and vegetables’ surface, leading to diarrhea or vomiting. 20 …”
Section: Introductionmentioning
confidence: 99%
“… 23 , 24 Fresh fruits and vegetables are often washed with tap water and then consumed directly. 19 However, due to the hydrophobic nature of many pesticides, tap water has a limited effect on their removal. 25 Therefore, scientists around the world are actively looking for chemicals to effectively remove pesticide residues from the surface of fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kong et al found that processing can effectively remove difenoconazole residues in tomatoes, in which washing and peeling can reduce the residue level by 99% (Kong et al 2012). Wu et al reported that processing of washing, juicing and cooking can effectively remove pesticide residues on the surface of kumquats, cucumbers and spinach (Wu et al 2019). The PF was ranged from 0.09 to 0.7.…”
Section: Introductionmentioning
confidence: 99%